Mind the Gap : City-Level Inflation Synchronization - Cevik, Serhan (IMF Working Papers; Working Paper, 2022)
The post-pandemic rise in consumer prices across the world has renewed interest in inflation dynamics after decades of global disinflation. This paper provides a spatial investigation of inflation synchronicity at the city level in Lithuania using disaggregated monthly data during the period 2000-2021. The empirical analysis provides strong evidence that (i) the co-movement of city-level inflation rates-estimated using the instantaneous quasi-correlation approach-is significantly weaker than the extent of synchronization suggested by the simple correlation analysis; (ii) there is substantial heterogeneity in the instantaneous quasi-correlation of inflation subcomponents between city pairs; and (iii) there are significant changes in the degree of city-level synchronization over time, reflecting important economic developments in history such as the global financial crisis, the adoption of euro, and the COVID-19 pandemic.